Androgen receptor expression in ductal carcinoma in situ of the breast: relation to oestrogen and progesterone receptors. Issue 1 (1st January 2002) - Selim, A-G A; El-Ayat, G; Wells, C A
Abstract : Aims: Ductal carcinoma in situ (DCIS) of the breast has been diagnosed increasingly since the advent of mammographic screening. In contrast to the situation in invasive breast carcinoma, there are no reports on androgen receptor (AR) status in DCIS and few reports on oestrogen (ER) and progesterone (PR) receptors. Methods: AR expression was examined in 57 cases of DCIS of the breast and correlated to the degree of differentiation and ER/PR status using immunohistochemical methods. Results: AR positivity was noted in 19 of the cases, whereas the other 38 cases were negative. There was no significant association between AR expression and the degree of differentiation of DCIS; three of the 13 well differentiated DCIS cases, 10 of the 19 intermediately differentiated cases, and six of the 25 poorly differentiated cases were positive (p = 0.093). However, a strong association was shown between the expression of ER (p < 0.0001) and PR (p = 0.002) and the degree of differentiation of DCIS. In addition, no significant association was found between the expression of AR and the expression of ER (p = 0.26) or PR (p = 0.57) in DCIS of the breast. Conclusions: A large number of cases of DCIS of the breast express AR and this may be associated with apocrine differentiation, which may impact on accurate typing of DCIS. Moreover, the expression of AR (but not ER or PR) in DCIS does not appear to be associated with the degree of differentiation.